هێماگەرایى و ڕەنگدانەوەى لە شیعرى گۆراندا - سالار, عبدالسلام (Sulaimani Journal for Humanities, 2003)
If we consider the romanticism a revolution to uproote the classicism, then we can consider the symboolism to be the depth of the romanticism. It's worth to mention that such an attempts, in this vary field. In the Kurdish literature are almost rare. There for, we have accomplished this research, in two chapters, as an attempt to light this dark corner in the Kurdish literature. The first chapter deals with the symbol as a literature term, erwiening some opinions about the consept of symbol, as well as mentioning the later authers negligence, to bring in something new, exept repeating the former authers opinions. Those opinions were summarized to that in symbol creation there must be two levels, the sentimental level and the meaning level, without any disconnection between them, as well as providing psycological resemblance between the two levels. Among these subjects delt with in this chapter:- The impact of the fantacy upon the poetry image, the role of the unconsious in the romanticists dreams, poetry language and music, the appearance of symbol as an ideology by the great authers like:- Bodlier, Moriase, Verlin and Steven Wallarrie, The second chapter deals with the beginning of poetry writing of Goran, then we traced the symbol as an ideology in his poems, then the conclusion that Goran in these poems, in which the symbolic ideology was nearly complete, begin to break the mistry of meaning, and revealing it to the reader.